From Incremental Dispossession to a Cumulative Land Grab: Understanding Territorial Transformation in India's North Karanpura Coalfield. Issue 6 (25th April 2019) - Oskarsson, Patrik; Lahiri‐Dutt, Kuntala; Wennström, Patrick
ABSTRACT: This article explores a great contradiction in rural land debates in India: on the one hand, explosive political contestation that is often able to halt proposed land acquisition; on the other, an unprecedented urban‐industrial expansion that is appropriating rural land. The authors argue that land grabbing for mining proceeds in an incremental manner, yet its cumulative effect leads to territorial transformation. To investigate this incremental appropriation, a temporal study of the North Karanpura coal mining tract in eastern India was conducted, combining remote sensing, interviews and official land‐use data. The results reveal a cumulative land grab of thousands of hectares from the late 1980s to the present day as open‐cut coal mines swallow up vast swathes of agricultural fields and forests. The political economy mechanism behind this immense land grab, which to date has gone undetected, consists of three phases: the reservation of the land as a coalfield with multiple coal blocks; the division of the blocks into separate mines; and the flexible expansion of individual mines wherever reduced resistance to land acquisition is encountered. This research indicates that an aggregate analysis of land dynamics can more robustly place the dramatic rearrangements of the Indian countryside within the international land grabbing debate.